Gastrointestinal tract bleeding in children with chronic cholestasis: Prevalence and risk factors in a tertiary referral hospital in Indonesia - Alatas, Fatima Safira; Nisa, Cholifatun (Paediatrica Indonesiana, 2023)
Background Cholestasis can lead to several complications, including portal hypertension and risk of gastrointestinal bleeding. However, there is a paucity of studies on the risk factors and prevalence of gastrointestinal tract bleeding in children with chronic cholestasis, particularly in Indonesia. Objective To determine the prevalence and risk factors for gastrointestinal bleeding in children with chronic cholestasis in Cipto Mangunkusumo Hospital, Jakarta, Indonesia. Methods This was a retrospective cohort study in a national referral hospital in Indonesia. Medical records of children with chronic cholestasis who visited the gastroenterohepatology outpatient clinic were collected for five years. Data on clinical symptoms, etiologies, and complications were obtained. Results A total of 97 participants were recruited on this study. The median age of the group was 0.31 years old. The most common causes of chornic cholestasis were biliary atresia, toxoplasma, other infections, rubella, cytomegalovirus, and herpes simplex virus (TORCH) infection, and urinary tract infection. Gastrointestinal bleeding occurred in 27.8% of patients, with hematemesis-melena being the most prevalent symptom. We found that liver cirrhosis, splenomegaly, thrombocytopenia, portal hypertension, and esophageal varices were all highly related with gastrointestinal bleeding. Splenomegaly, thrombocytopenia, and esophageal varices were associated with an increased risk of gastrointestinal bleeding in children with chronic cholestasis (P=0.018, P=0.008, and P=0.039, respectively). Conclusions The prevalence of gastrointestinal tract bleeding in children with chronic cholestasis is 27.8%, with splenomegaly, thrombocytopenia, and esophageal varices as significant risk factors.